Redesigning Medication Management in the Emergency Department: The Impact of Partnered Pharmacist Medication Charting on the Time to Administer Pre-Admission Time-Critical Medicines, Medication Order Completeness, and Venous Thromboembolism Risk Assessment - Tesfay Mehari Atey; Gregory M. Peterson; Mohammed S. Salahudeen; Tom Simpson; Camille M. Boland; Ed Anderson; Barbara C. Wimmer (MDPI AG, 2024)
In order to enhance interdisciplinary collaboration and promote better medication management, a partnered pharmacist medication charting (PPMC) model was piloted in the emergency department (ED) of an Australian referral hospital. The primary objective of this study was to evaluate the impact of PPMC on the timeliness of time-critical medicines (TCMs), completeness of medication orders, and assessment of venous thromboembolism (VTE) risk. This concurrent controlled retrospective pragmatic trial involved individuals aged 18 years and older presenting to the ED from 1 June 2020 to 17 May 2021. The study compared the PPMC approach (PPMC group) with traditional medical officer-led medication charting approaches in the ED, either an early best-possible medication history (BPMH) group or the usual care group. In the PPMC group, a BPMH was documented promptly soon after arrival in the ED, subsequent to which a collaborative discussion, co-planning, and co-charting of medications were undertaken by both a PPMC-credentialled pharmacist and a medical officer. In the early BPMH group, the BPMH was initially obtained in the ED before proceeding with the traditional approach of medication charting. Conversely, in the usual care group, the BPMH was obtained in the inpatient ward subsequent to the traditional approach of medication charting. Three outcome measures were assessed -the duration from ED presentation to the TCM's first dose administration (e.g., anti-Parkinson's drugs, hypoglycaemics and anti-coagulants), the completeness of medication orders, and the conduct of VTE risk assessments. The analysis included 321 TCMs, with 107 per group, and 1048 patients, with 230, 230, and 588 in the PPMC, early BPMH, and usual care groups, respectively. In the PPMC group, the median time from ED presentation to the TCM's first dose administration was 8.8 h (interquartile range: 6.3 to 16.3), compared to 17.5 h (interquartile range: 7.8 to 22.9) in the early BPMH group and 15.1 h (interquartile range: 8.2 to 21.1) in the usual care group (p < 0.001). Additionally, PPMC was associated with a higher proportion of patients having complete medication orders and receiving VTE risk assessments in the ED (both p < 0.001). The implementation of the PPMC model not only expedited the administration of TCMs but also improved the completeness of medication orders and the conduct of VTE risk assessments in the ED.